Community seed banks in China: achievements, challenges and prospects - Song, Xin; Guanqi Li; Vernooy, Ronnie; Song, Yiching (Frontiers Media, 2021)
The rich agrobiodiversity of China is under unprecedented threat, experiencing a dramatic loss of many valuable local varieties and wild relatives of main crops. The country's formal conservation system of ex situ genebanks faces serious challenges to address this loss. Community seed banks can play a key role to complement the conservation activities of these genebanks and provide other important collective goods, such as evolutionary services, but although they have been around for some 35 years in various parts of the world, in China they have a much shorter history. In recent years though the number has increased to almost 30 in 2020, in particular due to the efforts of the China Farmers' Seed Network. The community seed banks in the country are very diverse in terms of functions and services, forms of management and institutional linkages. Compared to the most common functions of community seed banks in other countries, China is bringing an important design innovation through two new functions: adding value to seed and produce through innovative marketing strategies, and building regional and national seed system linkages and fostering collaboration. The review of community seed banking not only provides rich empirical evidence, but also makes an important contribution to theory. Building on the achievements of community seed banking in the last decade, there is scope to scale this kind of very valuable agrobiodiversity conservation approach through more effective uptake and support by relevant national policies.